The Online Learning Activities during the Covid 19 Pandemic - M. Joharis Lubis; Liliana Puspa Sari (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2020)
The Covid 19 pandemic, which has spread throughout the world since December 2019 has changed the order of human life in all aspects, including education. The transition of offline to online learning is an absolute necessity. This paper aims to describe the ideas that related to the design of online learning management which is carried out when the long distance learning was implemented during the Covid 19 pandemic. The learning designs can be seen through the activities, which consist of: 1) filling in the learning material content, 2) tracking the students’ attendance, 3) presenting the learning materials, 4) conducting the discussion forums, and 5) providing the evaluation through assignments and quizzes.